Solid-state NMR of paired helical filaments formed by the core tau fragment tau(297-391) - Al-Hilaly, Youssra K.; Hurt, Connor; Rickard, Janet E.; Harrington, Charles R.; Storey, John M. D.; Wischik, Claude M.; Serpell, Louise C.; Siemer, Ansgar B. (Frontiers in Neuroscience, 2022)
Aggregation of the tau protein into fibrillar cross-β aggregates is a hallmark of Alzheimers’ diseases (AD) and many other neurodegenerative tauopathies. Recently, several core structures of patient-derived tau paired helical filaments (PHFs) have been solved revealing a structural variability that often correlates with a specific tauopathy. To further characterize the dynamics of these fibril cores, to screen for strain-specific small molecules as potential biomarkers and therapeutics, and to develop strain-specific antibodies, recombinant in-vitro models of tau filaments are needed. We recently showed that a 95-residue fragment of tau (from residue 297 to 391), termed dGAE, forms filaments in vitro in the absence of polyanionic co-factors often used for in vitro aggregation of full length tau. Tau(297-391) was identified as the proteolytic resistant core of tau PHFs and overlaps with the structures characterized by cryo-electron microscopy in ex-vivo PHFs, making it a promising model for the study of AD tau filaments in vitro. In the present study, we used solid-state NMR to characterize tau(297-391) filaments and show that such filaments assembled under non-reducing conditions are more dynamic and less ordered than those made in the presence of the reducing agent, DTT. We further report the resonance assignment of tau(297-392)+DTT filaments and compare it to existing core structures of tau.